Al-Imam Jalal al-Din al-Suyuti [849H-911H] - Ahmad, Abdul Rashid (Jurnal Usuluddin, 1999)
The article discusses the biography of a Muslim scholar known as al-Imam al-Suyuti [849H- 911H] and his contribution to the development of various disciplines as Tafsir al-Qur’an, al-Hadith, Fiqh, History, Arabic Language, Literature and Tasawwuf.